Preparation method of fusiform nano copper oxide
Through magnetic stirring and high-frequency ultrasonic dispersion technology, copper salt and alkali mixed solution are converted into micro-nano aerosols, and spindle-shaped nano-copper oxide powder is prepared through gas-phase-limited micro-zone mixing and hydrothermal reaction, which solves the problem of difficulty in preparing finer-grained copper oxide powders in the prior art and achieves higher catalytic activity and selectivity.
Patent Information
- Application Number
- CN202510121924.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-26
AI Technical Summary
It is difficult to prepare finer particle size copper oxide powders in the prior art, resulting in the failure of the catalytic activity and selectivity of nano-copper oxide.
Magnetic stirring and high-frequency ultrasonic dispersion technology are used to convert copper salt and alkali mixed solution into micro-nano aerosol, and spindle-shaped nano-copper oxide powder is prepared through gas-phase-limited micro-zone mixing and hydrothermal reaction.
The preparation of nano-copper oxide powder with finer particle size (100 nm ~ 1000 nm) was achieved, which improved catalytic activity and selectivity, and improved the preparation efficiency and control of product morphology.
Smart Images

Figure CN119551706A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of metal powder nanomaterial preparation, and in particular to a method for preparing spindle-shaped nano copper oxide. Background Art
[0002] Compared with traditional large-size copper oxide powder, nano-scale copper oxide powder has higher catalytic activity and selectivity, and shows significant advantages in other performance aspects. For example, nano-copper oxide with a particle size ranging from 1-100 nm exhibits unique physical and chemical properties in terms of magnetism, light absorption, chemical activity, thermal resistance, catalytic performance and melting point due to its unique surface effect, quantum size effect, volume effect and macroscopic quantum tunneling effect. These excellent properties make nano-copper oxide one of the widely used and highly concerned inorganic materials.
[0003] However, although there are many methods available to prepare CuO nanomaterials of different morphologies and sizes, the size of the prepared copper oxide powders is relatively large. How to obtain copper oxide powders with finer particle sizes has become an urgent problem to be solved.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In view of this, a method for preparing spindle-shaped nano copper oxide is provided, thereby overcoming, at least to a certain extent, the problem that copper oxide powder with a finer particle size cannot be obtained due to the limitations and defects of the relevant technology.
[0006] According to one aspect of the present disclosure, a method for preparing spindle-shaped nano copper oxide is provided, and the method for preparing spindle-shaped nano copper oxide comprises the following steps: Step 1: Under the action of magnetic stirring, the copper salt is configured as a copper precursor aqueous solution, and the base is configured as an alkaline mixed solution; Step 2: using a high-frequency ultrasonic dispersion device to convert the copper precursor aqueous solution into a micro-nano aerosol containing copper, and convert the alkaline mixed solution into a micro-nano aerosol containing a mixed alkali; Step 3, mixing the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol in a gas phase confined micro-region to obtain a copper-alkali mixed solution, and transferring the copper-alkali mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds; Step 4: performing solid-liquid separation, washing, drying and calcining on the nanoparticle solution containing the copper compound to obtain spindle-shaped nano copper oxide powder.
[0007] In an exemplary embodiment of the present disclosure, the copper salt includes at least one of copper chloride, copper acetate, copper sulfate or copper nitrate; The concentration of the copper precursor aqueous solution is less than or equal to 200 g / L.
[0008] In an exemplary embodiment of the present disclosure, the alkaline mixed solution is formed by mixing a strong alkaline solution and a weak alkaline solution; The strong alkaline solution is a sodium hydroxide solution; The weak alkaline solution includes at least one of sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water; The concentration of the alkaline mixed solution is less than or equal to 180 g / L; The pH value of the alkaline mixed solution is between 12 and 14, which is in a strong alkaline state.
[0009] In an exemplary embodiment of the present disclosure, the ultrasonic frequency of the high-frequency ultrasonic dispersion device is less than or equal to 4 MHz.
[0010] In an exemplary embodiment of the present disclosure, the copper-containing micro-nano aerosol is composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm; The micro-nano aerosol containing mixed alkali is composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm.
[0011] In an exemplary embodiment of the present disclosure, the gas phase confined micro-region mixing reaction is carried out at room temperature; In the process of gas phase confined micro-region mixing reaction, micro-region mixing needs to be carried out in the gas phase confinement less than 20 μm.
[0012] In an exemplary embodiment of the present disclosure, in the process of transferring the copper-alkali mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing a copper compound, the temperature of the hydrothermal reaction is 100° C. to 200° C.; The reaction time of the hydrothermal reaction is 1 h to 6 h. During the hydrothermal reaction, the pressure in the tetrafluoroethylene reactor is 3 MPa to 10 MPa.
[0013] In an exemplary embodiment of the present disclosure, in the process of solid-liquid separation of the nanoparticle solution containing the copper compound, the solid-liquid separation is carried out by centrifugal separation and / or suction filtration separation; In the process of washing the nanoparticles containing the copper compound after solid-liquid separation, the washing solution used is water and / or ethanol; In the process of drying the washed copper compound-containing nanoparticles, the drying method used is heat drying and / or cold drying; In the process of calcining the dried copper compound-containing nanoparticles, the calcination temperature used is 200°C to 500°C, and the atmosphere used in the calcination process is air.
[0014] In an exemplary embodiment of the present disclosure, the size of the obtained single spindle-shaped nano-copper oxide is 100 nm to 1000 nm, and the thickness is 20 nm to 80 nm.
[0015] In an exemplary embodiment of the present disclosure, the method for preparing the spindle-shaped nano copper oxide further comprises: using the prepared spindle-shaped nano copper oxide to prepare at least one of the following materials: a mechanical property material, an optical property material, and an electrical property material.
[0016] In a method for preparing spindle-shaped nano copper oxide provided in an exemplary embodiment of the present disclosure, on the one hand, under the action of magnetic stirring, copper salt is configured as a copper precursor aqueous solution, and alkali is configured as an alkaline mixed solution; then a high-frequency ultrasonic dispersion device is used to convert the copper precursor aqueous solution into a micro-nano aerosol containing copper, and the alkaline mixed solution is converted into a micro-nano aerosol containing a mixed alkali; then the copper-containing micro-nano aerosol and the micro-nano aerosol containing a mixed alkali are mixed in a gas phase confined micro-region to obtain a copper-alkali mixed solution, and the copper-alkali mixed solution is transferred to a polytetrafluoroethylene reaction vessel. A hydrothermal reaction is carried out in a reaction kettle to obtain a nanoparticle solution containing a copper compound; finally, the nanoparticle solution containing a copper compound is subjected to solid-liquid separation, washing, drying and roasting to obtain a spindle-shaped nano copper oxide powder. Since the preparation of nano copper oxide powder can be achieved on the basis of a micro-nano aerosol containing copper and a micro-nano aerosol containing a mixed alkali, and the micro-nano aerosol can be transmitted and dispersed over a long distance by spraying or gas flow, and the size of the micro-nano aerosol is less than 10 um, the prepared nano copper oxide powder with a finer particle size (length of 100 On the other hand, due to the high specific surface area of the micro-nano aerosol, it can be evenly distributed in the gas phase medium, providing more reaction and adsorption sites, thereby improving the efficiency of the mixing reaction, thereby improving the preparation efficiency of the nano copper oxide powder; on the other hand, the high-frequency ultrasonic dispersion device is used to convert the copper precursor aqueous solution into a copper-containing micro-nano aerosol, and the alkaline mixed solution is converted into a mixed alkali micro-nano aerosol, which not only greatly improves the transmission and diffusion rate of the copper source during the mixing process, but also effectively enhances the transmission and diffusion of the copper salt and the regulation of the micro-nano aerosol of the mixed alkali on the copper compound during the crystal growth process, which is conducive to the control of the product morphology and size.
[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0019] Figure 1 The flowchart of a method for preparing spindle-shaped nano-copper oxide according to an exemplary embodiment of the present disclosure is schematically shown.
[0020] Figure 2 The SEM image of the spindle-shaped nano copper oxide obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0021] Figure 3 The size distribution diagram of the spindle-shaped nano-copper oxide obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0022] Figure 4 The XRD (i.e., the spectrum of material structure analysis obtained by X-ray diffraction technology) diagram of the spindle-shaped nano copper oxide obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0023] Figure 5 The SEM image of the spindle-shaped nano-copper oxide obtained based on Example 3 according to an exemplary embodiment of the present disclosure is schematically shown.
[0024] Figure 6 The size distribution diagram of the spindle-shaped nano-copper oxide obtained based on Example 3 according to an exemplary embodiment of the present disclosure is schematically shown.
[0025] Figure 7 The SEM image of the spindle-shaped / spherical nano-copper oxide obtained based on Comparative Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0026] Figure 8 The SEM image of the coral-like nano copper oxide obtained based on Comparative Example 2 according to an exemplary embodiment of the present disclosure is schematically shown.
[0027] Fig. 9 The size distribution diagram of coral-like nano-copper oxide obtained based on Comparative Example 2 according to an exemplary embodiment of the present disclosure is schematically shown.
[0028] Fig.10A SEM image of copper oxide obtained based on Comparative Example 3 according to an exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.
[0030] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.
[0031] In recent years, the morphology of nanomaterials has attracted widespread attention in the field of materials science. Studies have shown that the size and morphology of nanoparticles have an important influence on their performance; in the process of practical application, the same nanomaterial often exhibits completely different physical and chemical properties due to differences in morphology. As an important inorganic material, copper oxide (CuO) has the advantages of abundant resources, stable chemical properties, non-toxicity and simple preparation. It can not only be used as a catalyst and its carrier, but also as an electrode activation material and rocket propellant, which makes copper oxide widely used in catalysis, superconductivity and ceramics. Furthermore, in the field of catalysis, copper oxide powder, as the main component of the catalyst, has shown excellent performance in a variety of catalytic reactions such as oxidation, hydrogenation, NO reduction, CO oxidation and hydrocarbon combustion.
[0032] However, although there are many methods to prepare CuO nanomaterials with different morphologies and sizes (i.e., to prepare CuO crystals with a particle size of 1-100 nm), there is no record of using mixed alkali as a morphology control agent to synthesize spindle-shaped CuO nanocrystals.
[0033] Based on this, the exemplary embodiment of the present disclosure first provides a method for preparing spindle-shaped nano copper oxide. Specifically, refer to Figure 1 As shown, the preparation method of the spindle-shaped nano copper oxide may include the following steps: Step S110. Under the action of magnetic stirring, the copper salt is configured as a copper precursor aqueous solution, and the base is configured as an alkaline mixed solution; Step S120. Using a high-frequency ultrasonic dispersion device, the copper precursor aqueous solution is converted into a micro-nano aerosol containing copper, and the alkaline mixed solution is converted into a micro-nano aerosol containing a mixed alkali; Step S130. The copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are mixed in a gas phase confined micro-region to obtain a copper-alkali mixed solution, and the copper-alkali mixed solution is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing a copper compound; Step S140: performing solid-liquid separation, washing, drying and calcining on the nanoparticle solution containing the copper compound to obtain spindle-shaped nano copper oxide powder.
[0034] In the above-described method for preparing spindle-shaped nano copper oxide, on the one hand, copper salt is configured as a copper precursor aqueous solution and alkali is configured as an alkaline mixed solution under the action of magnetic stirring; then the copper precursor aqueous solution is converted into a micro-nano aerosol containing copper by using a high-frequency ultrasonic dispersion device, and the alkaline mixed solution is converted into a micro-nano aerosol containing a mixed alkali; then the micro-nano aerosol containing copper and the micro-nano aerosol containing a mixed alkali are mixed in a gas phase confined micro-region to obtain a copper-alkali mixed solution, and the copper-alkali mixed solution is transferred to a polytetrafluoroethylene reactor. A hydrothermal reaction is performed to obtain a nanoparticle solution containing a copper compound; finally, the nanoparticle solution containing a copper compound is subjected to solid-liquid separation, washing, drying and roasting to obtain a spindle-shaped nano copper oxide powder; since the preparation of nano copper oxide powder can be achieved on the basis of a micro-nano aerosol containing copper and a micro-nano aerosol containing a mixed alkali, and the micro-nano aerosol can be transmitted and dispersed over long distances through spraying or gas flow, and the size of the micro-nano aerosol is less than 10 um, the prepared nano copper oxide powder with a finer particle size (length of 100 On the other hand, due to the high specific surface area of the micro-nano aerosol, it can be evenly distributed in the gas phase medium, providing more reaction and adsorption sites, thereby improving the efficiency of the mixing reaction, thereby improving the preparation efficiency of the nano copper oxide powder; on the other hand, the high-frequency ultrasonic dispersion device is used to convert the copper precursor aqueous solution into a copper-containing micro-nano aerosol, and the alkaline mixed solution is converted into a mixed alkali-containing micro-nano aerosol, which not only greatly improves the transmission and diffusion rate of the copper source during the mixing process, but also effectively enhances the transmission and diffusion of copper salts and the regulation of copper compounds by the micro-nano aerosol containing mixed alkali during crystal growth, which is conducive to the control of the product morphology and size.
[0035] Hereinafter, the method for preparing the spindle-shaped nano-copper oxide described in the exemplary embodiment of the present disclosure will be further explained and illustrated in conjunction with the accompanying drawings.
[0036] First, the technical implementation principle of the exemplary embodiment of the present disclosure is explained and illustrated. Specifically, the preparation method of the spindle-shaped nano copper oxide recorded in the exemplary embodiment of the present disclosure first prepares a copper salt aqueous solution and an alkaline mixed solution to create favorable conditions for the nano-scale dispersion of the copper salt and the regulation of crystal nucleation and growth, and then uses a high-frequency ultrasonic dispersion device technology to convert them into copper-containing micro-nano aerosols and mixed alkali-containing micro-nano aerosols formed by ultra-fine nano droplets, respectively, to construct a confined micro-region mixing environment, and then uses a hydrothermal synthesis method to optimize the reaction kinetic conditions of crystal growth by changing the reaction temperature, time, pressure and pH value, so as to strengthen the transmission and crystal growth mode during the reaction of the copper source and the mixed alkali, thereby obtaining nanoparticles of copper-containing compounds through nano-scale reactions, and then through solid-liquid separation, washing, drying and roasting, decomposition to obtain spindle-shaped nano copper oxide, and the morphology and size of nano copper oxide are regulated. It can be seen from this that the example embodiments of the present disclosure use a common water-soluble copper precursor as a copper source, and an ordinary alkaline mixed solution as a synergistic control agent for regulating crystal nucleation and growth. By changing factors such as reaction temperature, time, pressure and pH value, the lower nucleation rate and moderate growth rate in the crystal growth process are regulated, and preferential expansion is achieved in one direction, gradually forming a widened middle part and a contracted end, and finally achieving high-yield and controllable preparation of spindle-shaped nano copper oxide; at the same time, the preparation method of spindle-shaped nano copper oxide recorded in the example embodiments of the present disclosure is simple to operate, relatively mild reaction conditions, low production cost, environmentally friendly, and the prepared spindle-shaped nano copper oxide is assembled from a large number of nanosheets. This structure makes the material perform well in mechanical properties, optical properties and electrical properties, and can be widely used in important fields such as optoelectronic devices and sensors.
[0037] Among them, by changing factors such as reaction temperature, time, pressure and pH value, the lower nucleation rate and moderate growth rate during the crystal growth process are regulated, and the crystal preferentially expands in one direction, gradually forming a widened middle part and a contracted end, and finally achieving a high-yield and controllable preparation of spindle-shaped nano-copper oxide, which is manifested in the following aspects: (1) Temperature directly affects the nucleation rate and growth rate of the crystal; specifically, based on the specific experimental process, the following conclusions can be drawn: low temperatures of 100-200 degrees Celsius are conducive to slower crystal growth and easy formation of regular morphologies, such as spindles; further, at temperatures above 200°C, high temperatures promote rapid growth, which may lead to an increase in particle size or changes in morphology (such as transition from spindles to other morphologies); therefore, it is chosen to be carried out in an environment of 100-200°C to provide conditions for the formation of spindles. (2) The reaction time determines the growth stage of the crystal. Specifically, based on the specific experimental process, the following conclusions can be drawn: in a short time (for example, within 1 hour), copper oxide is mainly nucleated and can generate irregular particles, and the crystal has not yet formed a spindle-shaped structure; in a moderate time (for example, within 1-6 hours), growth is mainly used, which is conducive to the formation of a spindle-shaped structure and a more regular morphology; further, too long a time (for example, more than 6 hours) will cause the crystal to dissolve and grow again or form aggregates, destroying the spindle-shaped structure; therefore, the reaction is carried out for a period of 1-6 hours; (3) In a closed reactor, indirectly increasing the pressure to between 3 and 10 MPa by increasing the temperature is conducive to the stable growth of spindle-shaped nanostructures, while greater pressure may cause crystal agglomeration or abnormal structural morphology; (4) pH The pH value affects the degree of hydrolysis of copper ions in the solution and determines the nucleation and growth path of the crystal. In addition, in a weakly alkaline environment (i.e., when the pH value is low), the crystal growth rate will be inhibited to generate smaller crystals or other morphologies. However, in a strongly alkaline environment, a higher hydroxide ion concentration can promote the selective growth of crystals (such as preferential growth along specific crystal planes), provide balanced nucleation and growth conditions, and be conducive to the formation of a spindle-shaped structure.
[0038] It should also be noted here that the reason why the exemplary embodiments of the present disclosure need to use a high-frequency ultrasonic dispersion device to convert the copper precursor aqueous solution into a micro-nano aerosol containing copper, and convert the alkaline mixed solution into a micro-nano aerosol containing a mixed alkali, is because micro-nano aerosols have many advantages over ordinary solutions, which can be specifically reflected in: micro-nano aerosols can be transmitted and dispersed over long distances through spray or gas flow, and the size of micro-nano aerosols is less than 10um, with a high specific surface area, so they can be evenly distributed in the gas phase medium, can provide more reaction and adsorption sites, improve the efficiency of the mixed reaction, are more sensitive to changes in the external environment (such as temperature, humidity, pressure, etc.), can respond quickly, and can also effectively avoid phase separation or inhomogeneity that may occur in ordinary solutions, thereby making the morphology of the prepared materials controllable and the size is at the submicron level.
[0039] Secondly, Figure 1 The preparation method of the spindle-shaped nano copper oxide shown in the figure is further explained and illustrated. Specifically: In step S110, under the action of magnetic stirring, the copper salt is configured as a copper precursor aqueous solution, and the alkali is configured as an alkaline mixed solution.
[0040] Specifically, the copper salts recorded herein may include but are not limited to copper chloride, copper acetate, copper sulfate or copper nitrate, etc.; at the same time, the concentration of the obtained copper precursor aqueous solution needs to be less than or equal to 200 g / L; further, the alkaline mixed solution recorded herein may be a mixture of a strong alkaline solution and a weak alkaline solution; the strong alkaline solution recorded herein is a sodium hydroxide solution; the weak alkaline solution recorded herein may include but is not limited to sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water, etc.; at the same time, the concentration of the alkaline mixed solution needs to be less than or equal to 180 g / L, and the pH value of the alkaline mixed solution needs to be between 12 and 14 to ensure that the alkaline mixed solution is in a strong alkaline state.
[0041] It should be noted here that since the hydroxide ions in the alkaline mixed solution will undergo a coordination reaction with the metallic copper ions, the nucleation rate and growth direction of the copper oxide will be changed, allowing the material to grow from the core area, grow faster on specific crystal planes, and grow slower on other crystal planes, making the material form a shape that is wide in the middle and thin at both ends; at the same time, the concentration of the copper salt aqueous solution and the type and concentration of the screened alkali meet the needs of controlling the nucleation growth and morphology size of the product nano-copper oxide.
[0042] In step S120, a high-frequency ultrasonic dispersion device is used to convert the copper precursor aqueous solution into a micro-nano aerosol containing copper, and the alkaline mixed solution is converted into a micro-nano aerosol containing a mixed alkali.
[0043] Specifically, the ultrasonic frequency of the high-frequency ultrasonic dispersion device described herein needs to be less than or equal to 4 MHz; and the copper-containing micro-nano aerosol is composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm; the micro-nano aerosol containing mixed alkali is also composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm. It should be added here that the reason why the copper precursor aqueous solution needs to be converted into a copper-containing micro-nano aerosol and the alkaline mixed solution needs to be converted into a micro-nano aerosol containing mixed alkali by a high-frequency ultrasonic dispersion device is that the high-frequency ultrasonic dispersion device is conducive to converting the copper salt aqueous solution and the mixed alkali aqueous solution into an aerosol form that is easier to diffuse and has a smaller average particle size and a higher specific surface area, effectively strengthening the transmission and reaction kinetic conditions during the reaction of the copper source and the mixed alkali, and at the same time constructing a large number of micro-nano reaction areas, thereby inhibiting the agglomeration and ripening process of the nanoparticles of the copper compound, which helps to achieve control of the product morphology and size.
[0044] In step S130, the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are mixed in a gas phase confined micro-area to obtain a copper-alkali mixed solution, and the copper-alkali mixed solution is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds.
[0045] Specifically, the gas-phase confined micro-area mixing reaction recorded here is actually carried out at room temperature; at the same time, in the process of carrying out the gas-phase confined micro-area mixing reaction, micro-area mixing needs to be carried out in a gas-phase confinement of less than 20 μm; at the same time, in the process of preparing the copper-alkali mixed solution, the copper-containing micro-nano aerosol can also be replaced with a copper-containing aqueous solution having the same components; of course, the micro-nano aerosol containing the mixed alkali can also be replaced with a mixed alkali aqueous solution having the same components. In the process of actual application, it can be selected according to actual needs, and this example does not make special restrictions on this; further, in the process of transferring the copper-alkali mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution of copper compounds, the temperature of the hydrothermal reaction is 100 ℃~200 ℃; and the reaction time of the hydrothermal reaction is 1 h~6 h, and during the hydrothermal reaction, the pressure in the tetrafluoroethylene reactor is 3 MPa~10 MPa. It should be noted here that, since the reaction temperature has a significant effect on the rate and morphology of crystal growth, higher temperatures usually increase the diffusion rate of the solute and promote the growth of the material; therefore, when synthesizing a spindle-shaped structure, a moderate temperature can ensure a uniform growth rate, causing the middle to gradually widen and the two ends to gradually narrow; and, in the specific hydrothermal reaction process, the spindle-shaped structure can be achieved within the actual range of reaction conditions, and there is no special restriction on the specific value.
[0046] It is necessary to further explain here that, since the prepared copper-containing solution may include a copper-containing micro-nano aerosol and a copper-containing aqueous solution; the prepared mixed alkali-containing solution may include a mixed alkali-containing micro-nano aerosol and a mixed alkali aqueous solution; therefore, in the process of generating a copper-alkali mixed solution, it can be achieved based on the following methods: one implementation method is a mixed alkali-containing micro-nano aerosol + a copper-containing micro-nano aerosol; another implementation method is a mixed alkali-containing micro-nano aerosol + a copper-containing aqueous solution; another implementation method is a mixed alkali aqueous solution + a copper-containing micro-nano aerosol; and another implementation method is a mixed alkali aqueous solution + a copper-containing aqueous solution. In the process of actual application, the required implementation method can be determined according to actual needs, and this example does not impose any special restrictions on this.
[0047] In step S140, the nanoparticle solution containing the copper compound is subjected to solid-liquid separation, washing, drying and calcination to obtain spindle-shaped nano copper oxide powder.
[0048] Specifically, in the process of solid-liquid separation of the nanoparticle solution containing copper compounds, the solid-liquid separation method is centrifugal separation and / or suction filtration separation; in the process of washing the nanoparticles containing copper compounds after solid-liquid separation, the washing solution used is water and / or ethanol; in the process of drying the washed nanoparticles containing copper compounds, the drying method used is heat drying and / or cold drying; in the process of calcining the dried nanoparticles containing copper compounds, the calcination temperature used is 200°C~500°C, and the atmosphere used in the calcination process is air. At the same time, in the spindle-shaped nano copper oxide powder prepared based on the above method, the size of a single spindle-shaped nano copper oxide is 100 nm~1000 nm, and the thickness is 20 nm~80 nm.
[0049] At this point, the preparation method of spindle-shaped nano copper oxide described in the exemplary embodiment of the present disclosure has been fully realized. Based on the above-described contents, it can be known that, on the one hand, a common water-soluble copper precursor is used as the copper source, and an ordinary alkaline solution is used as a control agent to regulate the nucleation and growth of the crystal, and the copper source and the mixed alkali are converted into a micro-nano aerosol form for reaction, a three-dimensional spatial confined micro-area reaction condition is constructed, and the material transfer and reaction kinetic conditions are controlled, thereby realizing the controllable preparation of the morphology of spindle-shaped nano copper oxide; on the other hand, a micro-nano aerosol is obtained by high-frequency ultrasonic dispersion of a water-soluble copper source aqueous solution and a mixed alkali aqueous solution, which not only greatly improves the transmission and diffusion rate of the copper source during the mixing process, but also greatly improves the specific surface area of the droplets in the aerosol, effectively enhancing the transmission and diffusion of copper salts and the effect of the mixed alkali aqueous solution on copper compounds during the crystal growth process. On the other hand, the regulation of materials is conducive to the control of product morphology and size; on the other hand, the transmission through micro-nano aerosol is conducive to improving the dispersibility of the product; then the hydrothermal synthesis method is used to react, and the reaction kinetics of crystal growth is optimized by changing the reaction temperature, pressure, time and pH, so that the copper compound grows, and the morphology and size of the product copper-containing compound nanoparticles are precisely regulated. The morphology, size, uniformity and dispersibility of the prepared nano-copper oxide are significantly better than those of the traditional preparation method; further, by controlling the solid-liquid separation method, washing method, drying conditions and calcination method of the copper-containing compound nanoparticles, the crystal structure, morphology and size of nano-copper oxide are precisely regulated, which is helpful to obtain spindle-shaped nano-copper oxide.
[0050] Hereinafter, the method for preparing the spindle-shaped nano copper oxide described in the exemplary embodiment of the present disclosure will be further explained and illustrated in combination with specific embodiments. Specifically: Example 1 The method for preparing the spindle-shaped nano copper oxide described in the exemplary embodiment of the present disclosure may include the following steps: Step 1: prepare copper sulfate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and an alkaline mixed aqueous solution respectively; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is 12, which is in a strong alkaline state; Step 2: using a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to convert the copper salt aqueous solution and the alkaline mixed aqueous solution prepared in step 1 into copper-containing micro-nano aerosol and mixed alkali-containing micro-nano aerosol respectively; the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are both formed by ultra-fine nano droplets with an average particle size of less than 10 μm; Step 3, subjecting the mixed alkali-containing micro-nano aerosol and the copper-containing micro-nano aerosol obtained in step 2 to a gas phase confined micro-area mixing pre-reaction, and then rapidly transferring the mixed solution to a polytetrafluoroethylene reactor for a hydrothermal reaction at a reaction temperature of 130 ° C, a reaction time of 2 h, and a pressure in the reactor of 3 MPa. After cooling to room temperature, a nanoparticle solution containing a copper compound is collected; Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash it with 18.2 MΩ ultrapure water, dry it in an oven at 70°C, and then calcine it in an air atmosphere at 300°C to obtain spindle-shaped nano copper oxide powder; wherein the size of the obtained spindle-shaped nano copper oxide is about 400 nm, and the thickness of a single sheet is about 50 nm. The SEM image of the spindle-shaped nano copper oxide obtained in this way can be referred to Figure 2 As shown, the size distribution diagram of the spindle-shaped nano-copper oxide obtained based on this method can be referred to Figure 3 As shown, the XRD pattern of the spindle-shaped nano copper oxide obtained based on this method can be referred to Figure 4 shown.
[0051] At the same time, the alkaline aqueous solution in step 1 of this embodiment can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia water.
[0052] Example 2 The method for preparing the spindle-shaped nano copper oxide described in the exemplary embodiment of the present disclosure may include the following steps: Step 1: prepare copper sulfate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and an alkaline mixed aqueous solution respectively; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is 13, which is in a strongly alkaline state; Step 2: using a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to convert the copper salt aqueous solution and the alkaline mixed aqueous solution prepared in step 1 into copper-containing micro-nano aerosol and mixed alkali-containing micro-nano aerosol respectively; the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are both formed by ultra-fine nano droplets with an average particle size of less than 10 μm; Step 3, subjecting the mixed alkali-containing micro-nano aerosol and the copper-containing micro-nano aerosol obtained in step 2 to a gas phase confined micro-area mixing pre-reaction, and then rapidly transferring the mixed solution to a polytetrafluoroethylene reactor for a hydrothermal reaction at a reaction temperature of 130 ° C, a reaction time of 1 h, and a pressure in the reactor of 3 MPa. After cooling to room temperature, a nanoparticle solution containing a copper compound is collected; Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash it with 18.2 MΩ ultrapure water, freeze-dry it, and then calcine it in an air atmosphere at 350°C to obtain a spindle-shaped nano copper oxide powder; wherein the size of the obtained spindle-shaped nano copper oxide is about 200 nm, and the thickness of a single sheet is about 30 nm. It should be supplemented here that the SEM image of the spindle-shaped nano copper oxide, the size distribution map of the spindle-shaped nano copper oxide, and the XRD map of the spindle-shaped nano copper oxide obtained in this way are basically similar to the SEM image of the spindle-shaped nano copper oxide, the size distribution map of the spindle-shaped nano copper oxide, and the XRD map of the spindle-shaped nano copper oxide obtained in Example 1, and no further description will be given here.
[0053] At the same time, the alkaline aqueous solution in step 1 of this embodiment can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia water.
[0054] Example 3 The method for preparing the spindle-shaped nano copper oxide described in the exemplary embodiment of the present disclosure may include the following steps: Step 1: prepare copper sulfate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and an alkaline mixed aqueous solution respectively; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is 14, which is in a strong alkaline state; Step 2: using a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to convert the copper salt aqueous solution and the alkaline mixed aqueous solution prepared in step 1 into copper-containing micro-nano aerosol and mixed alkali-containing micro-nano aerosol respectively; the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are both formed by ultra-fine nano droplets with an average particle size of less than 10 μm; Step 3, subjecting the mixed alkali-containing micro-nano aerosol and the copper-containing micro-nano aerosol obtained in step 2 to a gas phase confined micro-area mixing pre-reaction, and then rapidly transferring the mixed solution to a polytetrafluoroethylene reactor for a hydrothermal reaction at a reaction temperature of 130 ° C, a reaction time of 5 h, and a pressure in the reactor of 3 MPa. After cooling to room temperature, a nanoparticle solution containing a copper compound is collected; Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2 MΩ ultrapure water, dry in an oven at 70°C, and then calcine in an air atmosphere at 400°C to obtain spindle-shaped nano copper oxide powder; wherein the size of the obtained spindle-shaped nano copper oxide is about 620 nm, and the thickness of a single sheet is about 60 nm. The SEM image of the spindle-shaped nano copper oxide obtained in this way can be referred to Figure 5 As shown, the size distribution diagram of the spindle-shaped nano-copper oxide obtained based on this method can be referred to Figure 6 shown.
[0055] At the same time, the alkaline aqueous solution in step 1 of this embodiment can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia water.
[0056] Comparative Example 1 The preparation method of copper oxide described in this embodiment comprises the following steps: Step 1: prepare copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and an alkaline mixed aqueous solution respectively; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is 14, which is in a strongly alkaline state; Step 2: using a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to convert the copper salt aqueous solution and the alkaline mixed aqueous solution prepared in step 1 into copper-containing micro-nano aerosol and mixed alkali-containing micro-nano aerosol respectively; the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are both formed by ultra-fine nano droplets with an average particle size of less than 10 μm; Step 3, subjecting the mixed alkali-containing micro-nano aerosol and the copper-containing micro-nano aerosol obtained in step 2 to a gas phase confined micro-area mixing pre-reaction, and then rapidly transferring the mixed solution to a polytetrafluoroethylene reactor for a hydrothermal reaction at a reaction temperature of 130 ° C, a reaction time of 2 h, and a pressure in the reactor of 3 MPa. After cooling to room temperature, a nanoparticle solution containing a copper compound is collected; Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2 MΩ ultrapure water, dry in an oven at 70°C, and then calcine in an air atmosphere at 300°C to obtain a spindle-shaped nano copper oxide powder, but accompanied by the generation of spherical particles; wherein the size of the obtained spindle-shaped nano copper oxide is about 400 nm, the thickness of a single sheet is about 50 nm, and the size of the spherical particles is about 20-30 nm; further, the SEM image of the spindle-shaped / spherical nano copper oxide obtained in this way can be referred to Figure 7 shown; based on Figure 7 It can be seen that although spindle-shaped nano-copper oxide can be obtained by using copper acetate as the copper salt, the obtained nano-copper oxide is impure.
[0057] At the same time, the copper salt aqueous solution recorded in step 1 of this comparative example can also be replaced by copper nitrate or copper chloride; the alkaline aqueous solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia water.
[0058] Comparative Example 2 The preparation method of copper oxide described in this embodiment comprises the following steps: Step 1: prepare copper sulfate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and an alkaline mixed aqueous solution respectively; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state; Step 2: using a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to convert the copper salt aqueous solution and the alkaline mixed aqueous solution prepared in step 1 into copper-containing micro-nano aerosol and mixed alkali-containing micro-nano aerosol respectively; the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol are both formed by ultra-fine nano droplets with an average particle size of less than 10 μm; Step 3, adding the mixed alkali-containing micro-nano aerosol obtained in step 2 to the copper-containing micro-nano aerosol to perform a gas phase confined micro-area mixing pre-reaction, and then quickly transferring the mixed solution to a polytetrafluoroethylene reactor for a hydrothermal reaction at a reaction temperature of 120 ° C for a reaction time of 2 h. After cooling to room temperature, a nanoparticle solution containing a copper compound is collected; Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2 MΩ ultrapure water, dry in an oven at 70°C, and then calcine at 300°C~400°C in an air atmosphere to obtain coral-like nano copper oxide powder; finally, reduce it at 150°C~200°C in a hydrogen atmosphere to obtain coral-like nano copper powder. The size of the coral-like nano copper oxide is about 183 nm, and the thickness of a single sheet is about 30 nm. The SEM image of the coral-like nano copper oxide obtained in this way can be referred to Figure 8 As shown, the size distribution diagram of the coral-like nano-copper oxide obtained based on this method can be referred to Fig. 9 shown; based on Figure 8 It can be seen that if the temperature of the hydrothermal reaction is lowered, spindle-shaped nano-copper oxide cannot be obtained.
[0059] At the same time, the copper salt aqueous solution in step 1 of this comparative example can also be replaced by copper acetate, copper nitrate or copper chloride; the alkaline aqueous solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia water.
[0060] Comparative Example 3: Step 1: Under the action of magnetic stirring, copper sulfate, sodium carbonate and sodium hydroxide are respectively prepared into a copper salt aqueous solution and an alkaline mixed aqueous solution; the concentration of the copper salt aqueous solution is 200 g / L, the concentration of the alkaline mixed aqueous solution is 180 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state; Step 2, the copper salt aqueous solution obtained in step 1 and the alkaline mixed aqueous solution are mixed for pre-reaction, and then the mixed solution is quickly transferred to a polytetrafluoroethylene reactor for hydrothermal reaction at a reaction temperature of 130 ° C, a reaction time of 6 h, and a pressure in the reactor of 3 MPa. After cooling to room temperature, a nanoparticle solution containing copper compounds is collected; Step 3: centrifuge the copper compound nanoparticle solution collected in step 2, wash with 18.2 MΩ ultrapure water, dry in an oven at 70°C, and then calcine in an air atmosphere at 400°C to obtain spindle-shaped copper oxide powder; wherein the size of the obtained spindle-shaped copper oxide is about 1-3 μm, and the thickness of a single sheet is about 200 nm. The SEM image of the spindle-shaped copper oxide obtained in this way can be referred to Fig.10 As shown; further, by Fig.10 It can be seen that the copper oxide obtained based on this comparative example has an uneven morphology, including not only spindle-shaped ones, but also spherical and shuttle-shaped ones, and the particle size is relatively large.
[0061] At the same time, the copper salt aqueous solution in step 1 of this embodiment can also be replaced by copper acetate, copper nitrate or copper chloride; the alkaline aqueous solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or ammonia. Further, it can be seen from Comparative Example 3 that in the state of non-micro-nano aerosol, if spindle-shaped copper oxide is required, the required reaction time is significantly increased and the size of the obtained spindle-shaped copper oxide is also larger.
[0062] It should be further explained here that in the hydrothermal reaction, Examples 1-3 and Comparative Examples 1-3 all adopted a reaction temperature of 130°C and a pressure of 3 MPa; however, in actual application, other temperatures within the range may also be used. The reaction temperature is proportional to the pressure value and can be selected according to actual needs. The present disclosure does not impose any special restrictions on this.
[0063] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0064] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
[0065] It should be understood that the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims. The description and embodiments are to be regarded as exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
Claims
1. A method for preparing spindle-shaped nano copper oxide, characterized in that: The preparation method of the spindle-shaped nano copper oxide comprises the following steps: Step 1: Under the action of magnetic stirring, the copper salt is configured as a copper precursor aqueous solution, and the base is configured as an alkaline mixed solution; Step 2: using a high-frequency ultrasonic dispersion device to convert the copper precursor aqueous solution into a micro-nano aerosol containing copper, and convert the alkaline mixed solution into a micro-nano aerosol containing a mixed alkali; Step 3, mixing the copper-containing micro-nano aerosol and the mixed alkali-containing micro-nano aerosol in a gas phase confined micro-region to obtain a copper-alkali mixed solution, and transferring the copper-alkali mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds; Step 4: performing solid-liquid separation, washing, drying and calcining on the nanoparticle solution containing the copper compound to obtain spindle-shaped nano copper oxide powder.
2. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The copper salt includes at least one of copper chloride, copper acetate, copper sulfate or copper nitrate; The concentration of the copper precursor aqueous solution is less than or equal to 200 g / L.
3. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The alkaline mixed solution is formed by mixing a strong alkaline solution and a weak alkaline solution; The strong alkaline solution is a sodium hydroxide solution; The weak alkaline solution includes at least one of sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water; The concentration of the alkaline mixed solution is less than or equal to 180 g / L; The pH value of the alkaline mixed solution is between 12 and 14, which is in a strong alkaline state.
4. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The ultrasonic frequency of the high-frequency ultrasonic dispersion device is less than or equal to 4 MHz.
5. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The copper-containing micro-nano aerosol is composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm; The micro-nano aerosol containing mixed alkali is composed of ultra-fine nano-droplets with an average size of less than or equal to 10 μm.
6. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The gas phase confined micro-region mixing reaction is carried out at room temperature; In the process of gas phase confined micro-region mixing reaction, micro-region mixing needs to be carried out in the gas phase confinement less than 20 μm.
7. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: In the process of transferring the copper-alkali mixed solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing a copper compound, the temperature of the hydrothermal reaction is 100° C. to 200° C.; The reaction time of the hydrothermal reaction is 1 h to 6 h. During the hydrothermal reaction, the pressure in the tetrafluoroethylene reactor is 3 MPa to 10 MPa.
8. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: In the process of solid-liquid separation of the copper compound-containing nanoparticle solution, the solid-liquid separation is carried out by centrifugal separation and / or suction filtration separation; In the process of washing the nanoparticles containing the copper compound after solid-liquid separation, the washing solution used is water and / or ethanol; In the process of drying the washed copper compound-containing nanoparticles, the drying method used is heat drying and / or cold drying; In the process of calcining the dried copper compound-containing nanoparticles, the calcination temperature used is 200° C. to 500° C., and the atmosphere used in the calcination process is air.
9. The method for preparing spindle-shaped nano copper oxide according to claim 1, characterized in that: The size of the obtained single spindle-shaped nano-copper oxide is 100 nm ~1000 nm and the thickness is 20 nm ~80 nm.
10. The method for preparing spindle-shaped nano copper oxide according to any one of claims 1 to 9, characterized in that: The method for preparing the spindle-shaped nano copper oxide also includes: The prepared spindle-shaped nano copper oxide is used to prepare at least one of the following materials: Mechanical properties materials, optical properties materials and electrical properties materials.
Citation Information
Patent Citations
Nanometer copper oxide with controllable morphology as well as preparation method and application of nanometer copper oxide
CN105523578A
Preparation method of nano ruthenium oxide with low cost, controllable granularity and high specific surface area
CN115321616A
Low-concentration aerosol generation method and low-concentration aerosol generation device
CN118341356A
Method for producing water dispersible cuo nanostructures
US20170066657A1
Method for making copper I oxide powders by aerosol decomposition
US5861136A